THE EFFECTIVENESS OF PROBLEM BASED WORKSHEET TO IMPROVE SENIOR HIGH SCHOOL STUDENTS’ CRITICAL THINKING SKILLS - Ningsyih, Suriya; Andayani, Yayuk; Hakim, Aliefman (Unnes Science Education Journal, 2018)
This research is a quasi-experimental with one group pretest-posttest design. The study aims to explore the effectiveness of using problem-based learning materials to improve students' critical thinking skills. The aspects of indicators of the critical thinking skills are a) interpretation, b) analysis, c) evaluation, d) inferential, and e) explanation. The subject of this research is the students of XI MIA class in a Senior High School in Mataram. There are three schools, which are SMAN 8 Mataram, SMAN 3 Mataram, and SMAK Kesuma Mataram. Each school has one class to represent. The researcher measured the effectiveness using N-gain test from the pretest and posttest result. The N-gain test resulted in 0.47. The score showed that the treatment was effective to improve students’ critical thinking skills.